Optimizing Student Practice Work Governance With The Information Technology Infrastructure Library (ITIL) V4 Approach - Istikoma; Huyearka Usady; Rangga Aditya Saputra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Practical Work (KP) process in the Information Systems Study Program at Muhammadiyah University of Pontianak still faces obstacles, such as the absence of reporting standards, limited partner information, monitoring difficulties, and an assessment system that is not yet transparent and integrated. This research aims to optimize KP service governance using the ITIL V4 approach with a focus on Service Request Management, Service Desk, and Continual Improvement. The research result is a website-based application that supports the KP process in an integrated manner, starting from determining location, managing daily logbooks, to online guidance documentation. This system also facilitates educational staff and supervisors to monitor student activities in real-time, so that the evaluation process becomes more objective and accountable. Testing with Black Box Testing ensures all functions run as required, while User Acceptance Testing (UAT) results in a satisfaction level for KP partners of 91%, students of 89%, and Study Program Admins of 95% (strongly agree category). This system is expected to improve efficiency, service quality and KP governance in a sustainable manner.